2021
DOI: 10.1039/d1sc02237g
|View full text |Cite
|
Sign up to set email alerts
|

An integrated mass spectrometry imaging and digital pathology workflow for objective detection of colorectal tumours by unique atomic signatures

Abstract: Tumours are abnormal growths of cells that reproduce by redirecting essential nutrients and resources from surrounding tissue. Changes to cell metabolism that trigger the growth of tumours are reflected in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 80 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…It has been reported that the level of trace elements in the human body influences the occurrence of gastrointestinal tumors in humans, which is accompanied by an increase in serum copper and a decrease in serum zinc during the formation of tumors (20). It has also been reported that serum copper and copper/zinc ratios are higher in patients with gastrointestinal tumors than in normal subjects (21,22), while zinc and calcium in the same cases are lower than in normal subjects (23), indicating that elevated serum copper and copper/zinc ratios may be risk factors for gastrointestinal tumors, while elevated serum zinc and calcium reduce the incidence of gastrointestinal tumors (24). Thus, both zinc and calcium were regarded as protective factors against the development of gastrointestinal tumors (25,26).…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that the level of trace elements in the human body influences the occurrence of gastrointestinal tumors in humans, which is accompanied by an increase in serum copper and a decrease in serum zinc during the formation of tumors (20). It has also been reported that serum copper and copper/zinc ratios are higher in patients with gastrointestinal tumors than in normal subjects (21,22), while zinc and calcium in the same cases are lower than in normal subjects (23), indicating that elevated serum copper and copper/zinc ratios may be risk factors for gastrointestinal tumors, while elevated serum zinc and calcium reduce the incidence of gastrointestinal tumors (24). Thus, both zinc and calcium were regarded as protective factors against the development of gastrointestinal tumors (25,26).…”
Section: Discussionmentioning
confidence: 90%
“…Nonlinear supervised learning models such as support vector machine (SVM), [ 128 , 129 , 130 ] random forest (RF), [ 131 , 132 , 133 ] and deep learning [ 134 , 135 , 136 , 137 , 138 , 139 ] are also widely used for classifying spectral data for spatial segmentation. The SVM algorithm finds a hyperplane with maximum margin to classify data.…”
Section: Computational Methods For Msi Data Analysismentioning
confidence: 99%
“…Data from other modalities provide complementary molecular or spatial information, which may be used to enhance the quality of MSI data or provide additional insights using more targeted analytical tools. MSI data have been coupled with histology, [ 91 , 133 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ] fluorescence microscopy, [ 188 , 189 , 190 , 191 ] Allen brain atlas, [ 107 , 192 ] topology, [ 193 , 194 , 195 ] electron microscopy, [ 196 , 197 ] Raman spectroscopy, [ 198 , 199 , 200 , 201 ] infrared spectroscopy, [ 202 ] magnetic resonance imaging, [ 93 , 203 ] and microsampling LC‐MS/MS analysis of proteins, transcripts, and genes. [ 164 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ] In these studies, computational approaches have been used for registration of the multimodal data.…”
Section: Computational Methods For Msi Data Analysismentioning
confidence: 99%
“…Quantitative imaging can also be achieved using the appropriate matrix-matched standard materials, either certified standard materials 91 or in-house standards. 92,93 Finally, many open-source or commercial software packages have been developed to process and reconstruct the enormous spatial imaging data from LA-ICP-MS. 94,95 Owing to these advances, new methods have been developed. Three-dimensional (3D) quantitative imaging of metals and metalloids has been realized by imaging successive slices of a sample with LA-ICP-MS and reconstructing the images into three dimensions.…”
Section: Single Cell Analysismentioning
confidence: 99%